2020
DOI: 10.1021/acs.jctc.0c00280
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Mechanisms of Communication Switching in the Hsp90-Cdc37 Regulatory Complexes with Client Kinases through Allosteric Coupling of Phosphorylation Sites: Perturbation-Based Modeling and Hierarchical Community Analysis of Residue Interaction Networks

Abstract: Understanding molecular principles underlying chaperone-based modulation of kinase client activity is critically important to dissect functions and activation mechanisms of many oncogenic proteins. The recent experimental studies have suggested that phosphorylation sites in the Hsp90 and Cdc37 proteins can serve as conformational communication switches of chaperone regulation and kinase interactions. However, a mechanism of allosteric coupling between phosphorylation sites in the Hsp90 and Cdc37 during client … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 139 publications
0
12
0
Order By: Relevance
“… 33 The important result of this analysis was a revelation that key regulatory sites that could dictate dynamic switching between conformational states of the SARS-CoV-2 spike trimer overlap with the high-centrality mediators of the interaction network that are also predicted to be effector centers with high allosteric potential ( Figures 10 and 11 ). To further examine the network properties, the hierarchical multilayer community decomposition was performed, and the community centrality metric 118 of the residue interaction networks was computed for distinct functional states of the SARS-CoV-2 spike trimer ( Figure 12 ). The community centrality profile revealed that network hubs that could bridge local modules in the locked state are located at the borders of the RBD regions ( Figures 12 A and 13 A).…”
Section: Resultsmentioning
confidence: 99%
“… 33 The important result of this analysis was a revelation that key regulatory sites that could dictate dynamic switching between conformational states of the SARS-CoV-2 spike trimer overlap with the high-centrality mediators of the interaction network that are also predicted to be effector centers with high allosteric potential ( Figures 10 and 11 ). To further examine the network properties, the hierarchical multilayer community decomposition was performed, and the community centrality metric 118 of the residue interaction networks was computed for distinct functional states of the SARS-CoV-2 spike trimer ( Figure 12 ). The community centrality profile revealed that network hubs that could bridge local modules in the locked state are located at the borders of the RBD regions ( Figures 12 A and 13 A).…”
Section: Resultsmentioning
confidence: 99%
“…Further, ATP binding is impacted by CK2 phosphorylation of the Hsp90b charged linker, which has been suggested to precede Hsp90: Cdc37 complex dissociation when ATP levels are low (84). Interestingly, CK2 phosphorylation of Cdc37-S13 promotes its association with kinases and recruitment of Hsp90 to kinase: Cdc37:Hsp90 ternary complexes for the chaperoning of kinase clients (46)(47)(48)152). Furthermore, sequential and ordered phosphorylation of the co-chaperone folliculin-interacting protein 1 (FNIP1) on several adjacent serine residues promotes its binding to Hsp90 and facilitates kinase and nonkinase client chaperoning (153).…”
Section: Serine/threonine Phosphorylationmentioning
confidence: 99%
“…This paper studies the self-healing system based on the structural model, summarizes the basic elements that the dynamic fault repair system needs, describes the formal language of the structural model, gives the application tools and related technical specifications, and gives the self-recovery flow diagram of the system. In view of the software development of an embedded system and the application of the structural model, the structure description of platform-dependent and platform-independent parts is given, and the realization of instantaneous fault recovery of the structural model in an embedded system is introduced with application cases [20,21]. Zavala et al [22] introduce the requirement of structural model style for a self-healing system and the method of a self-healing system based on style.…”
Section: Related Workmentioning
confidence: 99%